The Influence of the Implementation of the Discovery Learning Model Assisted by Powtoon Animated Video Media on Student Learning Outcomes in Buffer Solution Material - Br Bangun, Devrinawati; Syafriani, Dewi (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The quality of education can be improved through teaching methods that actively engage students, such as Discovery Learning. However, at SMAN 15 Medan, students still struggle to understand the topic of buffer solutions, resulting in exam scores that do not meet the Minimum Mastery Criteria (KKM). The use of Powtoon animation media in the Discovery Learning model is expected to help students understand abstract concepts and improve their learning outcomes. This study aims to evaluate the effect of the Discovery Learning model supported by Powtoon animation videos on students' learning outcomes in the topic of buffer solutions. The research population includes all 11th-grade students at SMAN 15 Medan, with a sample of class XI IPA 4 selected through the Simple Random Sampling method. The instrument used is a learning outcome test consisting of 20 multiple-choice questions. The hypothesis test using a one-sample t-test shows a significance value of 0.043, which is lower than α (0.05), thus accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). This indicates that students who learn using the Discovery Learning model assisted by Powtoon animation videos successfully achieve the Minimum Mastery Criteria of 78 or KKM (78). Additionally, the N-gain analysis shows an average score of 0.72, with a percentage of 71.68% falling into the high category. These results indicate that the implemented learning model is quite effective in improving students' learning outcomes on the topic of buffer solutions. The learning outcomes of students taught using the Discovery Learning model assisted by Powtoon animation videos in the 11th-grade science class (MIPA) exceed the Minimum Mastery Criteria of 78 or KKM (78). There is an influence of the Discovery Learning model assisted by Powtoon animation media on students' learning outcomes.Keywords: Discovery Learning Model, Learning Outcomes, Powtoon Animated Video Media, Buffer Solution.DOI: 10.23960/jppk.v13.i3.30478